The Effectiveness of Teaching Materials for Graphic Organizers in Reading in Elementary School Students - Kurniaman, Otang; Zufriady, Zufriady (FKIP-Universitas Riau, 2019)
A teacher must be able to develop teaching materials inlearning because it is a professional demand that can provide meaningfuland enjoyable learning. The purpose of this study was to describe theeffectiveness of developing graphic organizer teaching materials inreading in grade 4 of elementary school. The graphic organizer is alearning media used to read learning. This is a development research withconsisting of 4 stages namely defining, designing, developing, anddisseminating research results. Aspects namely need analysis and studentanalysis. In needs analysis, some analyzes were carried out coveringcurriculum, concepts, and assignments. While in the analysis of studentslooking at the suitability of teaching materials developed with the level ofdevelopment of students. The design phase of teaching materials wasmade to plan the implementation of learning indicators, the averageindicator was 95, and the learning objectives aspect was 93. Thedevelopment phase was tested in SDN 38 Kota Pekanbaru with anaverage reading ability of 87.5, so it can be concluded that theeffectiveness of teaching materials for graphic organizer in reading isvery decent to use.